Katholische Juden? - Eine Ethnografie zu den Xuetes auf Mallorca - Riemenschneider, Christian (Universitätsverlag Göttingen, 2016)
This ethnography focuses on the descendants of Majorca´s forcedly baptized Jews, the so called Xuetes. Well into the 20th century these catholic Majorcans were marginalized and persecuted as Jews by the majority population. So far the history of the Xuetes was understood as a "past that doesn`t want to go by", cast as an apology for church and state. This book sheds light on a present where some Xuetes still feel "neither fish nor fowl". For the first time, Xuetes and Non-Xuetes themselves hold the floor. The result is not a "faith triumphant" as is the title of a contemporary account on the collective forced baptism but a story of coping with trauma. Theoretical approaches to trauma, taboo, memory and identity facilitate a detailed presentation of identity formation with all its toil, zest and pursuit of knowledge.